Identification of Competitive Strengths 5 Best Marketplace in DKI Jakarta - Alma Kurniawan; Rudy C. Tarumingkeng; Gidion P. Adirinekso (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
Increasingly competitive competition arises because of digital technology in business. One of Michael Porter's famous competitive theories is regarding the competitive force. There are five components in it: bargaining power of customers, bargaining power of suppliers, the threat of new entrants, threat of substituted products and services, and rivalry among existing competitors. Using quantitative methods, this study will discuss Michael Porter’s theory components that affect business competition in the digital era. The sample selection for this research is spread over all people of DKI Jakarta who have at least one marketplace. According to the seller/store owner's perspective, the five components that affect Marketplace business competition in the digital marketing era are rivalry of competitors, bargaining power of customers, the threat of new entrants, bargaining power of suppliers, the threat of substitute product, and service. Meanwhile, according to buyers of goods in the marketplace, the five components that affect Marketplace business competition in the digital marketing era are rivalry of competitors, the threat of substituted products and services, bargaining power of customers, and bargaining power of suppliers a threat of new entrants. From the results of this study, it is suspected that Michael Porter's theory can be applied in business competition in the digital era. For further research, the author will discuss whether it is true that Michael Porter's approach is still relevant to be applied according to practitioners and marketing strategists.